Pengembangan Multimedia Interaktif Pada Tema 7 Kelas I Sekolah Dasar - Oji Fahrozi; Hendra Budiono (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2022)
The aim of this development is to produce products in the form of interactive multimedia in the form of valid and practical learning applications. The results of the development were then tested at SDN 166/I Olak Rambahan in class I with a total of 14 students. In this research, the development design model used is the ADDIE development model where there are 5 main phases or stages, including: analysis, design, development, implementation, and evaluation. When translated into Indonesian, it means analyzing, designing, developing, implementing and evaluating. This research was conducted at SDN 166/1 Olak Rambahan in Batanghari Regency. Research data was obtained from material validation and language validation. The results of the research show that the level of validation by media or teaching aids experts is 100% which is included in the very valid category, by material experts 100% which is included in the very valid category, the practicality of the teacher's response is 98% which is included in the very practical category and the participants' responses students based on the results of interviews with students who stated that the application used was easy to use and there were learning videos that did not make them bored, and students were interested in learning to use the learning application and it could be concluded that the application was categorized as practical.